Electrocardiographic Abnormalities and QTc Prolongation in Lupus Patients on Hydroxychloroquine in Tehran, Iran - Parisa Delkash; Soheila Sadeghi; Fatemeh Omidi (Novelty in Biomedicine, 2025)
Background: Hydroxychloroquine, a commonly prescribed treatment for systemic lupus erythematosus (SLE), has been associated with potential cardiac complications, including QTc prolongation. QTc prolongation increases the risk of arrhythmias and sudden cardiac death. This study aimed to evaluate electrocardiographic (ECG) abnormalities in Iranian SLE patients receiving hydroxychloroquine treatment.